Poly-γ-Glutamic Acid (PGA)-Producing Bacillus Species Isolated from Kinema, Indian Fermented Soybean Food - Chettri, Rajen; Bhutia, Meera O.; Tamang, Jyoti P. (Frontiers in Microbiology, 2016)
Kinema, an ethnic fermented, non-salted and sticky soybean food is consumed in the eastern part of India. The stickiness is one of the best qualities of good kinema preferred by consumers, which is due to the production of poly-γ-glutamic acid (PGA). Average load of Bacillus in kinema was 107 cfu/g and of lactic acid bacteria was 103 cfu/g. Bacillus spp. were screened for PGA-production and isolates of lactic acid bacteria were also tested for degradation of PGA. Only Bacillus produced PGA, none of lactic acid bacteria produced PGA. PGA-producing Bacillus spp. were identified by phenotypic characterization and also by 16S rRNA gene sequencing as Bacillus subtilis, B. licheniformis and B. sonorensis.